On the properties of financial analyst earnings forecasts: some new evidence - Bolliger, Guido (My University, 2003)
The importance of information in the formation process of security prices has a long history. The dissemination of information can take on different forms depending on the legal constraints. However, in all developed financial markets, financial analysts play a prominent role in collecting, analysing and diffusing information. Financial analysts typically supply future earnings estimates and stock picking advices in the form of recommendations. Earnings estimates are the essential part of security valuation by analysts and investors. They have even become an integral part of financial reporting in the financial press. Early research has accumulated evidence that these estimates are optimistically biased. More recently, empirical studies have found that analysts' optimistic bias is lessening, that its extent differs across analysts, firm characteristics and countries. Broadly speaking, this dissertation investigates the determinants of financial analyst forecasts bias. In the first essay, I examine the relative accuracy of European financial analysts' earnings forecasts and its determinants. I show that the results obtained for US analysts can not be generalised to European analysts who face a seemingly different job market as well as several different institutional and economic environments. In the second essay, I investigate the influence of financial analysts' location on their performance. More precisely, I examine the relative performance of local versus foreign analysts on Latin American stock markets. I find foreign analysts to be more timely and more accurate than their local counterparts. In addition, I document stronger price reactions after foreign analysts' forecast revisions than after those of local analysts. The third essay is related to the declining pattern of financial analyst forecast bias. In particular, I investigate whether US CEOs compensation arrangements give CEOs incentives to manipulate analysts' expectations downward in order to release earnings that meet or beat market estimates. The results confirm this hypothesis. I document a strong link between expectations management and the relevant option component of CEO compensation, bonus plans, and the percentage of the company's shares owned by the CEO who manages it.
Thèse de doctorat : Université de Neuchâtel, 2003 ; 1715